Reduced ERA‐I Forecasting Skill During Forbush Decreases - Jacob Svensmark (Geophysical Research Letters)
Abstract Correlations between week‐long cosmic ray flux perturbations and terrestrial cloud cover have previously been identified. Still, uncertainty persists on whether the cloud response is due to a physical link involving cosmic rays or caused by random weather fluctuations. To investigate this further, we compare a time series of daily assimilated weather observations from the ERA‐INTERIM system with its forecasts. This probes whether the presumed cloud signal originates from weather fluctuations consistent with the ERA‐INTERIM model. We find that the ERA‐INTERIM forecasting system performed significantly worse during rapid cosmic ray suppressions over the last 20 years, supporting the hypothesis that cosmic rays influence terrestrial cloud formation.